Surface Water Yield Model Part H: Application and Economic Analysis of Storage Reservoirs - Reddy, K.S.; Bhattacharya, A.K.; Mishra, K.; Selvarajan, S. (Journal of Soil and Water Conservation, 2022)
A surface water yield model (SWY MOD) developed by Reddy (1993) was used with long term rainfall data in kharif season to generate information on the temporal distribution of the availability of stored runoff in small reservoirs of a few selected inicrowatersheds in Chotanagpur region of Upper Damodar Valley, Bihar. The availability of runoff in the reservoirs was compared with the estimated gross deficits in the water requirements of three commonly grown crops in the study area, viz, paddy, maize and pigeon pea. On the basis of this comparison and using linear programming model, several crop plans were studied and an optimal crop plan was identified. The optimal crop plan comprised growing maize and pigeon pea on 18.69 ha and 0.33ha of the total irrigable area respectively. The benefit-cost ratio for 5 to 15 years amortization periods varied from 4.4 to 6.7 and 5.6 to 7.9 correspondingly when the reservoir cost is included and excluded from the analysis.